2016
DOI: 10.1080/14712598.2017.1256388
|View full text |Cite
|
Sign up to set email alerts
|

The importance of correctly timing cancer immunotherapy

Abstract: Introduction:The treatment options for cancer-surgery, radiotherapy and chemotherapy-are now supplemented with immunotherapy. Previously underappreciated but now gaining strong interest are the immune modulatory properties of the three conventional modalities. Moreover, there is a better understanding of the needs and potential of the different immune therapeutic platforms. Key to improved treatment will be the combinations of modalities that complete each other's shortcomings. Area covered: Tumor-specific T-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 130 publications
1
17
0
Order By: Relevance
“…Additionally, the timing, dose, and localization of immunomodulators plays a critical role in determining the magnitude and phenotype of the resultant immune response. 5,10,65,81,82 Yet, locally administered biomacromolecules, including nucleic acids, typically rapidly clear from the injection site, which not only limits local bioavailability but can also result in systemic distribution with an increased risk of toxicity. 37,39,80 These challenges have motivated the development of delivery technologies for controlled and sustained release of nucleic acid immunotherapeutics.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the timing, dose, and localization of immunomodulators plays a critical role in determining the magnitude and phenotype of the resultant immune response. 5,10,65,81,82 Yet, locally administered biomacromolecules, including nucleic acids, typically rapidly clear from the injection site, which not only limits local bioavailability but can also result in systemic distribution with an increased risk of toxicity. 37,39,80 These challenges have motivated the development of delivery technologies for controlled and sustained release of nucleic acid immunotherapeutics.…”
Section: Introductionmentioning
confidence: 99%
“…With the advent of immunotherapy, new prospects have been opened up for successful cancer treatment. Increasing evidence shows that the efficacy of immunotherapeutic drugs can be enhanced by combined applications, which are believed to support the anti-tumor response at multiple sites [ 1 , 2 ]. Further advances include optimization of immunotherapy timing as well as deeper investigation and better understanding of tumor microenvironment biology [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The median follow-up was 11.8 months (range: [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. At the time of analysis, one patient (treated at "most favourable" time-position) had died 22 months after SBRT-PATHY because of causes other than cancer.…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…Currently, some studies have described an association between the radiation-induced lymphopenia with poor oncologic outcome, indicating that radiotherapy using large volumes and multiple daily fractions can lead to immunosuppression [8,9]. On the other side, some studies have shown potential therapeutic benefits by eventual ablation of regulatory ("suppressor") T cells with limited (single-dose) systemic therapies [10][11][12] given "at the right time" in order to selectively ablate those suppressor T cells while sparing the effector T cells. Thus, suggesting that the accurate timing of limited therapy may play a major role in treatment efficacy.…”
Section: Introductionmentioning
confidence: 99%